A study of statutory provisions relating to kidnapping: the Penal Code, the Kidnapping Act 1961 other relevant statutes / Siti Nurida Sehoo, Nor Hayati Osman and Nor Hayati Osman - Sehoo, Siti Nurida; Osman, Nor Hayati; Jusoh, Norliza (2008)
The research is about the study relating to kidnapping provisions that used to govern the kidnapping offence namely Penal Code and Kidnapping Act 1961. Basically, the idea of the research is to know the non-existence on the definition of kidnapping in Kidnapping Act 1961. Even though the statute governed all the crime or act relating to kidnapping, but when it comes to the definition, it must be referred to Penal Code. The research is also will deal with the punishments imposed on the offenders once they are convicted. Since both statutes provides for its own punishments, the research will determine the methods or solutions that had been used by the judges in deciding the kidnapping offence's case. In finding all the relevant information, the research also has to look at the legal standing on kidnapping offence in other countries and also comparing the standing with the current position in Malaysia. Apart from that, the position under Islamic regarding kidnapping offence also been discussed. In addition, kidnapping in other countries also known as abduction and it is considered as less serious offence if compared with Malaysia situation. Thus, all the objectives that had been proposed are to be achieved. As for conclusion, there are needs to do research in this topic because it will bring benefit in future legal system. For instance, it will help judges in deciding kidnapping cases in future and give clear description about the kidnapping offence.